Fertoeibacter niger gen. nov., sp. nov. a novel alkaliphilic bacterium of the family Rhodobacteraceae. Issue 3 (18th March 2021) - Szuróczki, Sára; Abbaszade, Gorkhmaz; Buni, Dominika; Bóka, Károly; Schumann, Peter; Neumann-Schaal, Meina; Vajna, Balázs; Tóth, Erika
Abstract : Three Gram-stain-negative, non-motile, oxidase- and catalase-positive, rod-shaped, black, facultative phototrophic bacterial strains, RG-N-1a T, DMA-N-7a and RA-N-9 were isolated from the water sample from Lake Fertő/Neusiedler See (Hungary). Phylogenetic analysis based on the 16S rRNA gene sequences revealed that the strains form a distinct linage within the family Rhodobacteraceae and their closest relatives are Tabrizicola piscis K13M18 T (96.32%) followed by Cypionkella psychrotolerans PAMC 27389 T (96.25%). The novel bacterial strains prefer alkaline environments and grow optimally at 23–33 °C in the presence of NaCl (1–2 w/v%). Bacteriochlorophyll a was detected. Cells contained exclusively ubiquinone Q-10. The major cellular fatty acids were C18 : 1 ω7 c, C19 : 1 iso ω5 c, C18 : 0 3-OH and C18 : 1 ω 7 c 11-methyl. The polar lipid profile contains diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylcholine, an unidentified phospholipid and four unidentified lipids. The assembled draft genome of RG-N-1a T had 33 contigs with N50 values 315 027 nt, 96× genome coverage, total length of 4 326 551 bp and a DNA G+C content of 64.9%. Genome-based calculations (genome-to-genome distance and DNA G+C percentage) and pairwise amino acid identity (AAI <73.5%) indicate that RG-N-1a T represents a novel genus. RG-N-1a T (=DSM 108317 T =NCAIM B.02647 T ) is suggested as the type strain of a novel genus and species in the family Rhodobacteraceae, for which the name Fertoeibacter niger gen. nov., sp. nov. is proposed.